The transfer of heavy metals from the water "in the dish", through fish - Dorian Gabriel Neidoni; Stefania Gheorghe; Sorina Claudia Negrea; Adina Pacala; Alexandru Pahomi (Romanian Journal of Ecology & Environmental Chemistry)
The current work aimed to highlight the impact produced by copper intoxication on the freshwater fish species Cyprinus carpio L. Besides quantifying the degree of metal accumulation in the fish tissues, we also proposed a different approach, namely to see how much the thermal handling/preparation affects the heavy metal concentration in the final product. For this, boiling and frying techniques of intoxicate fish fillets were used. The results showed a considerable percentage decrease of copper in fish fillets subjected to thermal preparation compared to those not thermally treated (raw).